1996
DOI: 10.1073/pnas.93.22.12496
|View full text |Cite
|
Sign up to set email alerts
|

DNA-mediated immunization in a transgenic mouse model of the hepatitis B surface antigen chronic carrier state.

Abstract: Transgenic mice expressing the sequences coding for the envelope proteins of the hepatitis B virus (HBV) in the liver have been used as a model of the HBV chronic carrier state. We evaluated the possibility of inducing a specific immune response to the viral envelope antigens and thus potentially controlling chronic HBV infection. Using HBV-specific DNA-mediated immunization in this transgenic model, we show that the immune response induced after a single intramuscular injection of DNA resulted in the complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
3
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(83 citation statements)
references
References 33 publications
2
77
3
1
Order By: Relevance
“…To date, several constructs have been tested in different animal models (mice and nonhuman primates) in which Abs (15,16), CD4 ϩ T cell proliferative responses (17), and CD8 ϩ CTL were induced (18 -20). Results obtained in HBsAg-transgenic mice, an animal model for HBV chronic carriers, suggested that DNA-based immunization against HBsAg could induce or increase the immune response in chronically infected patients (6,17). These results have been further confirmed in duck and woodchuck as animal models for hepadnavirus infection (21,22).…”
Section: H Epatitis B Virus (Hbv)mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several constructs have been tested in different animal models (mice and nonhuman primates) in which Abs (15,16), CD4 ϩ T cell proliferative responses (17), and CD8 ϩ CTL were induced (18 -20). Results obtained in HBsAg-transgenic mice, an animal model for HBV chronic carriers, suggested that DNA-based immunization against HBsAg could induce or increase the immune response in chronically infected patients (6,17). These results have been further confirmed in duck and woodchuck as animal models for hepadnavirus infection (21,22).…”
Section: H Epatitis B Virus (Hbv)mentioning
confidence: 99%
“…Several observations suggest that cytotoxic T cells are required for the viral clearance, although lysis of infected hepatocytes is unlikely to be the only mechanism through which CD8 ϩ T cells exert their anti-viral effect. Indeed, in transgenic mouse models for HBV gene expression and/or replication, CTL mediate not only the down-regulation of viral gene expression (5,6) but also the control of viral replication (7). This phenomenon is probably due to the anti-viral effects of Th1 cytokines (i.e., IFN-␥, IFN-␣, IFN-␤, and TNF-␣) secreted by CD8 ϩ T cells after antigenic stimulation or following a concomitant viral infection (8).…”
Section: H Epatitis B Virus (Hbv)mentioning
confidence: 99%
“…DNAvaccination is probably a more potent method to induce antigen-specific immunity than protein or peptide vaccine. It is reported that immunization with plasmids that contain HBsgene can profoundly reduce the production of HBsAgin transgenic mice that produce HBsAgin their livers (14). This may be a promising approach to cure patients with chronic HBVinfection, and more detailed study should be done to increase the efficacy and to elucidate the mechanismof viral clearance.…”
Section: Vaccinationmentioning
confidence: 99%
“…Younossi et al 1 suggest that ascertainment bias due to an interest in iron storage disorders explains the high prevalence of HFE mutations in the series from Brisbane 2 and Boston. 4 In these later two studies, most but not all iron overload in nonalcoholic steatohepatitis (NASH) was associated with mutations of the HFE gene. We would argue that the high prevalence of HFE mutations and mild iron overload in these studies reflect the ethnic background of patients referred to these centers and the interactions of these HFE mutations and the factors that result in NASH.…”
Section: Iron and Fibrosis In Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…The theoretical basis for immune therapy in chronic HBV infection comes from animal models suggesting the possibility of using hepatitis B surface and core epitopes 2,3 or DNA immunizations 4,5 to stimulate immune responses. Moreover, pilot studies of vaccine-specific therapy in humans with chronic hepatitis B showed encouraging results.…”
Section: Immune Therapy Of Hepatitis B Virus Chronic Infectionmentioning
confidence: 99%